The early phase of Crohn's disease in a young girl - Zhong-Xin Yang; Wei-Wen Tang; Wei Liu (Archives of Clinical Gastroenterology - Peertechz Publications, 2021)
A 21-year-old girl was transferred to our hospital with 1-year history of abdominal pain and vomiting that had progressed over the preceding 3 weeks. She had presented to the local hospital with a 3-day history of fever before presentation. Physical examination revealed normal vital signs and mild periumbilical tenderness with active bowel sounds. Laboratory tests of the blood confirmed a white-cell count of 13,400 per cubic millimeter (reference range, 4000 to 10,000). Computed Tomography (CT) of the abdomen revealed lymphnode enlargement of ileocecal region.